Cancer-Associated Fibroblasts Facilitate Squamous Cell Carcinoma Lung Metastasis in Mice by Providing TGFβ-Mediated Cancer Stem Cell Niche - Shi, Xueke; Luo, Jingjing; Weigel, Kelsey J.; Hall, Spencer C.; Du, Danfeng; Wu, Fanglong; Rudolph, Michael C.; Zhou, Hongmei; Young, Christian D.; Wang, Xiao-Jing (Frontiers in Cell and Developmental Biology, 2021)
Cancer-associated fibroblasts (CAFs) have been shown to enhance squamous cell carcinoma (SCC) growth, but it is unclear whether they promote SCC lung metastasis. We generated CAFs from K15.KrasG12D.Smad4-/- mouse SCCs. RNA expression analyses demonstrated that CAFs had enriched TGFβ signaling compared to normal tissue-associated fibroblasts (NAFs), therefore we assessed how TGFβ-enriched CAFs impact SCC metastasis. We co-injected SCC cells with CAFs to the skin, tail vein, or the lung to mimic sequential steps of lung metastasis. CAFs increased SCC volume only in lung co-transplantations, characterized with increased proliferation and angiogenesis and decreased apoptosis compared to NAF co-transplanted SCCs. These CAF effects were attenuated by a clinically relevant TGFβ receptor inhibitor, suggesting that CAFs facilitated TGFβ-dependent SCC cell seeding and survival in the lung. CAFs also increased tumor volume when co-transplanted to the lung with limiting numbers of SCC cancer stem cells (CSCs). In vitro, CSC sphere formation and invasion were increased either with co-cultured CAFs or with CAF conditioned media (which contains the highest TGFβ1 concentration) and these CAF effects were blocked by TGFβ inhibition. Further, TGFβ activation was higher in primary human oral SCCs with lung metastasis than SCCs without lung metastasis. Similarly, TGFβ activation was detected in the lungs of mice with micrometastasis. Our data suggest that TGFβ-enriched CAFs play a causal role in CSC seeding and expansion in the lung during SCC metastasis, providing a prognostic marker and therapeutic target for SCC lung metastasis.